Education Reform in the Kyrgyz Republic - Lessons from PISA - Hou, Dingyong (World Bank, Washington, DC, 2012)
The Kyrgyz Republic spends tremendous resources on education. More than 20 percent of total public expenditure, but outcomes are poor. The Kyrgyz Republic was ranked last in math, science and reading among nations that participated in the 2006 and 2009 rounds of the Program for International Student Assessment (PISA). The National Sample-Based Achievement Test (NSBA) showed the same trend of underachievement. A joint World Bank Organization for Economic Cooperation and Development (OECD) review was initiated to unlock the major gaps between the educational aspirations of the Kyrgyz Republic and the achievement of reforms in a number of policy areas. Systemic, sector-wide reforms for reversing the trend of high spending, low impact and poor results were recommended.